Impact of epidural analgesia on labor progression and maternal-fetal outcomes: a comparative observational study - Tran , Doan Tu; Nguyen , Khoa Bao; Nguyen , Vu Quoc Huy; Le , Minh Tam (Tạp chí Y Dược Huế, 2025)
Background: Epidural analgesia (EA) is widely considered the gold standard for pain relief during labor. This study aimed to evaluate the impact of EA on labor progression and maternal-neonatal outcomes in women undergoing vaginal delivery. Methods: A prospective cohort study was conducted from June 2024 to February 2025. Term pregnant women in spontaneous labor with singleton, cephalic fetuses (37⁰–41⁶ gestational weeks) were enrolled and categorized by parity (nulliparous or multiparous) and EA status. Labor progress was monitored using the World Health Organization (WHO) Labor Care Guide (LCG) (2018), focusing on the active phase of the first stage and the second stage. Primary outcomes included duration of labor stages, maternal complications, and neonatal outcomes. Results: In nulliparous women, EA significantly prolonged both the active phase of the first and second stages of labor compared to those without EA (p < 0.05). EA initiated at < 5 cm cervical dilation was associated with a longer second stage (37.7 ± 30.4 vs. 25.9 ± 22.6 minutes, p = 0.022). In multiparous women, the duration of labor did not differ significantly between the EA and control groups (p > 0.05). EA use was not associated with increased rates of severe perineal lacerations, postpartum hemorrhage, uterotonic use, or low APGAR scores in either group. Conclusions: Epidural analgesia provides effective pain relief during labor without increasing the risk of adverse maternal or neonatal outcomes. However, it may prolong labor duration in nulliparous women, especially when initiated early (< 5 cm cervical dilation). Individualized counseling and careful monitoring are recommended to ensure safety and optimize outcomes.